Observation of manganese deposits in the New England Seamount Chain during Atlantis Cruise 280 - Pratt, Richard M; Thompson, Stephen L (Woods Hole Oceanographic Institution, 1962)
Reports on ATLANTIS Cruises 280 and 281 to the New England Seamount Chain are combined here. . A continuous bathymetric survey was run on both cruises, with profiles across several seamounts. A series of dredge and camera stations were made. They are dicussed in this report. Also included are photographs representative of each camera lowering and photographs of dredged material.